Canva and Geogebra-Assisted Problem Based Learning Worksheet to Improve Students’ Mathematical Problem Solving Ability and Learning Interest on Senior High School - Deanisa Noviana Lukmana; Jozua Sabandar; Asep Ikin Sugandi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
The low levels of students’ mathematical problem-solving ability and interest in learning, particularly in the topic of the Three-Variable Linear Equation System (SPLTV), become the primary context of this study. This research aims to develop learning tools in the form of Student Worksheets (LKPD) and learning media based on the Problem-Based Learning model, assisted by the Canva and Geogebra, that are valid, practical, and effective. The research method used was Research and Development (R&D), following the nine development stages of the Borg and Gall model. Subjects involved Grade X and Grade XI students from SMAN 1 Batujajar and SMAN 2 Cimahi. Instruments included validation sheets, teacher and student response questionnaires (Likert scale), a mathematical problem-solving ability test, and a student learning interest attitude scale. Results showed that the developed learning tools were considered very valid based on the assessments of material and media experts, and met the criteria of being very practical based on the responses given by teachers and students. In addition, the learning tools were effective, as indicated by increases in N-gain scores, improved classical mastery criteria in the experimental class compared with the control class, and a significant improvement in the student learning interest attitude scale. Statistical tests confirmed that the use of these learning tools significantly improved students’ problem-solving ability and interest in learning compared with conventional learning. The Problem-Based Learning mathematics learning tools, assisted by Canva and GeoGebra, are feasible and effective as an innovative solution for senior high school learning.